Sex differences in ambulatory blood pressure levels, control, and phenotypes of hypertension in kidney transplant recipients. Issue 2 (27th September 2021) - Korogiannou, Maria; Sarafidis, Pantelis; Theodorakopoulou, Marieta P.; Alexandrou, Maria Eleni; Xagas, Efstathios; Argyris, Antonis; Protogerou, Athanase; Ferro, Charles J.; Boletis, Ioannis N.; Marinaki, Smaragdi
Abstract : Objectives: Ambulatory blood pressure (BP) control is worse in men compared with women with chronic kidney disease (CKD) and this may partially explain the faster CKD progression in men. This is the first study investigating possible sex differences in prevalence, control and phenotypes of hypertension in kidney transplant recipients (KTRs) with office-BP and 24-h ambulatory BP monitoring (ABPM). Methods: This cross-sectional study included 136 male and 69 female stable KTRs who underwent office-BP measurements and 24-h ABPM. Hypertension thresholds for office and ambulatory BP were defined according to the 2017 ACC/AHA and 2021 KDIGO guidelines for KTRs. Results: Age, time from transplantation, eGFR and history of major comorbidities did not differ between groups. Office SBP/DBP levels were insignificantly higher in men than women (130.3 ± 16.3/77.3 ± 9.4 vs. 126.4 ± 17.8/74.9 ± 11.5 mmHg; P  = 0.118/0.104) but daytime SBP/DBP was significantly higher in men (128.5 ± 12.1/83.0 ± 8.2 vs. 124.6 ± 11.9/80.3 ± 9.3 mmHg; P  = 0.032/ P  = 0.044). No significant between-group differences were detected for night-time BP. The prevalence of hypertension was similar by office-BP criteria (93.4 vs. 91.3%; P  = 0.589), but higher in men than women with ABPM (100 vs. 95.7%; P  = 0.014). The use of ACEIs/ARBs and CCBs was more common in men. Office-BP control was similar (43.3 vs. 44.4%, P  = 0.882), but 24-h control was significantly lower in men than women (16.9 vs. 30.3%; P  = 0.029). White-coat hypertension was similar (5.1 vs. 7.6%; P  = 0.493), whereas masked hypertension was insignificantly more prevalent in men than women (35.3 vs. 24.2%; P  = 0.113). Conclusion: BP levels, hypertension prevalence and control are similar by office criteria but significantly different by ABPM criteria between male and female KTRs. Worse ambulatory BP control in male compared with female KTRs may interfere with renal and cardiovascular outcomes.